Evaluation of Antibiotic Prescribing Practices and Antimicrobial Sensitivity Patterns in Urinary Tract Related Infectious Diseases in Pediatric Patients - Sirajudeen S. Alavudeen; Anas Ali Asiri; Shatha Abdulrahman Fageeh; Ahmed Abdoh Aljarie; Mir Javid Iqbal; Noohu Abdulla Khan; Fauzia Tabassum; Mohamed Rahamathulla; Umme Hani; Md Sayeed Akhtar (Frontiers Media S.A., 2021)
Complications of urinary tract infections (UTIs) like kidney failure and septicaemia develop once infections spread from the upper urinary tract to other parts of the body by haematogenous dissemination and they pose great health and economic burden to the countries. This retrospective study was conducted among 132 patients with bacterial UTIs in the inpatient department of tertiary care hospital in Abha, Saudi Arabia. During the study period, Escherichia coli (E. coli) and Klebsiella pneumonia (K. pneumonia) along with other 15 different bacteria were isolated. A significant difference (P < 0.05) was observed between the male and female children population in different age groups. We observed fever (84.09%) as a major symptom (P < 0.05), and seizure (9%) was reported as a major concomitant condition among UTI cases. Around 31.82% of E. coli was found to be the most common uropathogens in pediatric cases followed by 25% in K. pneumoniae. E. coli was observed to be more susceptible (92.86%) to amikacin, ceftriaxone, levofloxacin, ertapenem, gentamycin, meropenem, piperacillin-tazobactam, tigecycline, and ceftazidime. However, meropenem, tigecycline, and amikacin were observed to be effective in 100% of cases of K. pneumoniae. Meanwhile, cephalosporins were the most commonly prescribed drug category among different classes of drugs. Almost 99% of pediatric cases, based on their age, were admitted to the ward, and drugs were administered intravenously. We concluded that microbiology laboratory evidence on the causative organisms and choice of treatment together allows tailoring appropriate treatment regimens in conjunction with clinical experiences.